2008
DOI: 10.1093/jnci/djn171
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 6-Sulfatoxymelatonin Levels and Risk of Breast Cancer in Postmenopausal Women

Abstract: Results from this prospective study provide evidence for a statistically significant inverse association between melatonin levels, as measured in overnight morning urine, and invasive breast cancer risk in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 44 publications
7
91
2
Order By: Relevance
“…Epidemiological studies have shown that melatonin decreases the risk of developing breast and other kinds of cancer (Kliukiene et al, 2001;Kloog et al, 2008;Schernhammer et al, 2008Schernhammer et al, , 2009Schernhammer et al, , 2009Schernhammer et al, , 2010Alpert et al, 2009). However, very little is known about the molecular mechanisms by which melatonin accomplishes its anticancer effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies have shown that melatonin decreases the risk of developing breast and other kinds of cancer (Kliukiene et al, 2001;Kloog et al, 2008;Schernhammer et al, 2008Schernhammer et al, , 2009Schernhammer et al, , 2009Schernhammer et al, , 2010Alpert et al, 2009). However, very little is known about the molecular mechanisms by which melatonin accomplishes its anticancer effects.…”
Section: Discussionmentioning
confidence: 99%
“…It is worthy to note that blind women produce higher levels of melatonin as their retina receives less light and therefore their pineal gland is less induced to reduce melatonin production. Two prospective control studies nested in larger cohorts have been recently published (Schernhammer et al, 2008(Schernhammer et al, , 2010. The first study, conducted within the Hormones and Diet in the Etiology of Breast Cancer Risk (ORDET) cohort, tested the concentration of a melatonin metabolite, 6-sulfatoxymelatonin (aMT6s) in 178 postmenopausal women with incident breast cancer and in 710 matched controls (Schernhammer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lower melatonin level was associated with an increased risk of breast cancer (Schernhammer and Hankinson, 2005;Schernhammer et al, 2008). Melatonin may have an inhibitory effect on gonadal function, including the synthesis and secretion of sex hormones, by promoting the release of gonadaotropin-releasing hormone (Martin and Klein, 1976;Aleandri et al, 1996); it also exerts an antiproliferative effect on breast cancer cell lines (Blask et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Four out of five prospective cohort studies among women without night work have shown increased risk of breast cancer related to low urine levels of the melatonin metabolite, 6-sulfatoxymelatonin in morning spot samples or 24 hour samples (12)(13)(14)(15)(16). Unfortunately there are only few studies that in some detail outline the melatonin exposure profile (peak, amplitude, duration, timing) among people working night shifts (17)(18)(19)(20) except among nurses working in fastforward-rotating shifts (21).…”
Section: Light Circadian Rhythms and Melatoninmentioning
confidence: 99%